Mixing of Brand Cancellation Lawsuits and Brand Infringement Lawsuits - Yosi Esa Hadi Saputra; Henny Marlyna (Indonesian Journal of Multidisciplinary Science, 2023)
The mixing between trademark infringement lawsuits and annulments has made it an issue in trademark law enforcement, thus making it an excuse for the Supreme Court to overturn the Court's ruling. It raises new cases from the procedural law of brand law enforcement, but the dimensions of brand protection must still be upheld. For this reason, it is necessary to explain the difference between a trademark infringement lawsuit and trademark cancellation, as well as the reasons for the supreme court judge in decision No.525K/Pdt.Sus-HKI/2020 annulling judgment No. 4/Pdt.Sus-HKI/Merek/2019/PN Niaga.Sby regarding the mixing between the trademark infringement lawsuit and the cancellation of the brand. The Panel of Judges of the Surabaya District Court in Decision Number 4/Pdt.Sus-HKI/Merek/2019/PN-Niaga.Sby seems to prioritize its establishment based on the perspective of legal expediency, thus categorizing the defendant's actions as trademark violations. The Panel of Judges of the Supreme Court prioritizes its establishment based on the perspective of order, so the reason for overturning the decision of the Surabaya District Court considering the mixing between the infringement lawsuit and the cancellation of the brand is based on legal certainty. It is necessary to discuss the pattern of application of the law that converges between trademark cancellation lawsuits and trademark infringement and advise the Supreme Court to make guidelines in the form of regulations aimed at the judiciary that contain provisions on the criteria between annulment lawsuits and trademark infringement, so that they can be a reference for judges in the proceedings.